Structural and electronic properties of the active site of [ZnFe] SulE - Moubarak, Samah; Rippers, Yvonne; Elghobashi-Meinhardt, Nadia; Mroginski, Maria Andrea (Frontiers in Molecular Biosciences, 2022)
The function of the recently isolated sulerythrin (SulE) has been investigated using a combination of structural and electronic analyses based on quantum mechanical cal-culations. In the SulE structure of Fushinobu et al., isolated from a strictly aerobic ar-chaeon, Sulfolobus tokadaii, a dioxygen-containing species was tentatively included at the active site during crystallographic refinement although the substrate specificity of SulE remains unclear. Studies have suggested that a structurally related enzyme, rubrerythrin, functions as a hydrogen peroxide reductase. Since SulE is a truncated version of rubrerythrin, the enzymes are hypothesized to function similarly. Hence, using available X-ray crystallography data (1.7 Å), we constructed various models of SulE containing a ZnII-Fe active site, differing in the nature of the substrate specificity (O2, H2O2), the oxidation level and the spin state of the iron ion and in the protonation states of the coordinating glutamate residues. Also, the substrate H2O2 is modeled in two possible configurations, differing in the orientation of the hydrogen atoms. Over-all, the optimized geometries with an O2 substrate do not show good agreement with the experimentally resolved geometry. In contrast, excellent agreement between crys-tal structure arrangement and optimized geometries is achieved considering a H2O2 substrate and FeII in both spin states, when Glu92 is protonated. These results sug-gest that the dioxo species detected at the [ZnFe] active site of sulerythin is H2O2-, ra-ther than an O2 molecule in agreement with experimental data indicating that only the diferrous oxidation state of the dimetal site in rubrerythrin reacts rapidly with H2O2. Based on our computations we propose a possible reaction pathway for substrate binding at the ZnFeII site of SulE with a H2O2 substrate. In this reaction pathway Fe or another electron donor, such as NAD(P)H, catalyzes the reduction of H2O2 to water at the zinc-iron site.